Low Levels of Dehydroepiandrosterone Sulfate in Younger Burnout Patients - Lennartsson, Anna-Karin; Theorell, Töres; Kushnir, Mark M.; Jonsdottir, Ingibjörg H. (PloS one, 2015)
Dehydroepiandrosterone sulphate (DHEA-s) is an anabolic protective hormone of importance for maintenance of health. DHEA-s levels peak in young adults and decline thereafter with age. DHEA-s has previously been shown to be lower in individuals reporting prolonged stress. This study investigates DHEA-s levels in patients with clinical burnout, a disorder caused by long-term psychosocial stress. 122 patients (51% men) and 47 controls (51% men) in the age 25-54 years were included in the study. DHEA-s levels were compared between patients and controls in the whole sample and within each of the three 10-year-interval age groups. In the youngest age group (25-34 years), DHEA-s levels were on average 25% lower in the patients (p = 0.006). The differences in DHEA-s levels between patients and controls were more pronounced among female than male participants (on average 32% and 13% lower, respectively). There were no differences in DHEA-s levels between patients and controls in the age group 35-44 years (p = 0.927) or 45-54 years (p = 0.897) or when analyzing all age groups together (p = 0.187). The study indicates that levels of the health promoting "youth" hormone DHEA-s are low in younger burnout patients. The fact that younger adults have much higher DHEA-s levels and more pronounced inter-subject variability in DHEA-s levels than older individuals might explain why burnout status differentiates patients from controls only among the youngest patients included in this study.